2014
DOI: 10.2337/db13-0835
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SREBP Transcriptional Activity by a Boron-Containing Compound Improves Lipid Homeostasis in Diet-Induced Obesity

Abstract: Dysregulation of lipid homeostasis is intimately associated with obesity, type 2 diabetes, and cardiovascular diseases. Sterol regulatory-element binding proteins (SREBPs) are the master regulators of lipid biosynthesis. Previous studies have shown that the conserved transcriptional cofactor Mediator complex is critically required for the SREBP transcriptional activity, and recruitment of the Mediator complex to the SREBP transactivation domains (TADs) is through the MED15-KIX domain. Recently, we have synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
0
31
1
Order By: Relevance
“…The three SREBP isoforms, SREBP-1a, SREBP-1c and SREBP-2, play different roles in lipid synthesis. Studies using transgenic and knockout mice suggest that SREBP-1c plays an essential role in the regulation of most lipogenic genes involved in fatty acid and TAG synthesis (Zhao et al, 2014). The present study showed significant increase in SREBP-1c mRNA level as well as FAS activity in the liver tissues of HFD fed rats when compared to treated groups, however dandelion and or milk thistle supplementations attenuated this increase in treated groups.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The three SREBP isoforms, SREBP-1a, SREBP-1c and SREBP-2, play different roles in lipid synthesis. Studies using transgenic and knockout mice suggest that SREBP-1c plays an essential role in the regulation of most lipogenic genes involved in fatty acid and TAG synthesis (Zhao et al, 2014). The present study showed significant increase in SREBP-1c mRNA level as well as FAS activity in the liver tissues of HFD fed rats when compared to treated groups, however dandelion and or milk thistle supplementations attenuated this increase in treated groups.…”
Section: Discussioncontrasting
confidence: 50%
“…Sterol regulatory element binding proteins (SREBPs) are master transcription factors for de novo lipogenesis (Zhao et al, 2014). The three SREBP isoforms, SREBP-1a, SREBP-1c and SREBP-2, play different roles in lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Such a concept is supported by the results of recent studies on SREBP inhibitors in animal models [43][44][45][46]. Here, we briefly describe the SREBP maturation pathway, elaborate key molecular mechanisms involved in the classical triad of hyperglycemia, hyperinsulinemia, and hypertriglyceridemia, and discuss beneficial effects of four SREBP inhibitors as well as potential caveats associated with their use.…”
mentioning
confidence: 86%
“…The fourth study used a compound that targeted the transcriptional activity of SREBPs [46]. Previous studies have shown that recruitment of the Mediator of RNA polymerase II transcription subunit 15 (MED15)-Kinase-inducible domain interacting (KIX) domain of the mediator complex to the SREBP transactivation domain is necessary for transcriptional activities of SREBPs [76].…”
Section: Bf175mentioning
confidence: 98%
“…15,16 Sterol regulatory elements (SRE) are cis-regulatory elements present in the promoters of genes that represent the key steps of lipid biosynthesis pathways. The defined SREBP-target genes can be functionally categorized into two groups.…”
Section: Introductionmentioning
confidence: 99%